2019
DOI: 10.1021/acs.cgd.9b00150
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function of MamC Loop and Its Effect on the in Vitro Precipitation of Biomimetic Magnetite Nanoparticles

Abstract: MamC, an integral protein of the magnetosome membrane, has recently been proposed as a strong candidate to produce biomimetic (magnetosome-like) magnetite nanoparticles that could be used as an alternative to magnetosomes in different applications such as nanocarriers. The secondary structure of the protein contains two helical transmembrane domains connected by an α-helical loop oriented toward the magnetosome lumen. In this loop, the residues Glu66 and Asp70 seem to be responsible for a template effect that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In fact, they have demonstrated their potential as promising drug nanocarriers, even when embedded in liposomes [ 14 , 15 , 34 ], and as hyperthermia agents [ 15 , 23 , 35 ], which opens the possibility for combined therapy using the same nanoplatform. MamC modulates the nucleation and growth of the crystal by both template and ionotropic effects [ 15 , 36 ] and remains attached to the nanoparticles, forming a nanocomposite of 95 wt% magnetite + 5 wt% MamC. Such control of MamC on magnetite synthesis in vitro results in magnetic nanoparticles of different sizes and morphologies and thus magnetic properties, compared to those of chemically produced ones, and in nanoparticles with novel surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they have demonstrated their potential as promising drug nanocarriers, even when embedded in liposomes [ 14 , 15 , 34 ], and as hyperthermia agents [ 15 , 23 , 35 ], which opens the possibility for combined therapy using the same nanoplatform. MamC modulates the nucleation and growth of the crystal by both template and ionotropic effects [ 15 , 36 ] and remains attached to the nanoparticles, forming a nanocomposite of 95 wt% magnetite + 5 wt% MamC. Such control of MamC on magnetite synthesis in vitro results in magnetic nanoparticles of different sizes and morphologies and thus magnetic properties, compared to those of chemically produced ones, and in nanoparticles with novel surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of Bereczk-Tompa et al . 43 and being the iron binding by negatively charged amino acids (in extended surfaces) a less specific process than the binding of previously formed nuclei, magnetite nucleation induced by the ionotropic effect is probably kinetically favoured in the case of MamC 44 . HRTEM images of MamC-mediated magnetite crystals in Lopez-Moreno et al .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it was MamC, and not Mms6, the protein that had more input determining the size of the crystals. Several studies 26,29,30,41,44,45 have shown the effect of MamC on the size of the magnetite crystals formed in the presence of the protein and had demonstrated the importance of the conformation of MamC loop in properly controlling such a size. Therefore, the template effect, rather than the ionotropic effect seems to stand as the key factor controlling nucleation and the size of the final crystals under limited iron conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ionotropic (i.e. iron-affinity) effect of MamC does not give sufficient ground for the role of this protein in biomineralization [84,91,92]. MamC must exert a template effect in magnetite formation [84].…”
Section: Microbes Inspire Chemistry: Biomimetic Synthesis Of Artificimentioning
confidence: 99%
“…MamC must exert a template effect in magnetite formation [84]. In the MM, MamC is constituted by two transmembrane domains connected by alpha-helical looping, which contacts the forming magnetite within the magnetosome vesicle lumen [92]. The distance between iron-interacting residues Glu66 and Asp70 of the alpha-helical looping matches the iron interatomic distance within the magnetite surface plane.…”
Section: Microbes Inspire Chemistry: Biomimetic Synthesis Of Artificimentioning
confidence: 99%